Delta dynamics: a numerical investigation of the inhibiting effects of tidal range and significant wave height on delta development - Sloan, Ewan (2025)
In this thesis, the process-based numerical model Delft3D 4 (Deltares, 2021a,b) is used to investigate how tidal range and significant wave height affect, and potentially prevent, the development of river deltas within a range of idealised simulations. In order to reduce the parameter space and hence simplify analysis, focus is restricted to just the effects of wave height and tidal range, following the assumption that the effects of discharge are relatively linear and predictable—i.e. lower river sediment flux equates to reduced likelihood of delta formation. The primary objective of the work, therefore, is to determine if there exist limits of significant wave height and / or tidal range beyond which delta formation is prevented, and to elucidate the relevant processes where (if) this is found to be the case.